Pengembangan Multimedia Pembelajaran Interaktif Berbasis Corel Draw X7 Dalam Pembuatan Kaligrafi Pada Yayasan Cerdas Murni - REZA KURNIA LESMANA; RASYID RIDHO; ARYA PRATAMA DAMANIK; CAHAYA MUZADDIDAH; ALI IKHWAN (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
Education is an effort to develop oneself both physically and spiritually related to skills, intelligence, and personality as well as creativity and improving soft skills, especially for teenagers at the high school level. In today's technologically advanced era, many teenagers have interests, especially in the field of graphic design which refers to multimedia learning. Multimedia-based learning media can be used to increase students' understanding of using the Corel Draw X7 application. Half of the pure intelligent TKJ 10-2 class members have a high interest in graphic design or Corel draw X7 subjects. But they are not proficient in using the features in Corel Draw X7 in making calligraphy. So that this research aims to introduce the features of Corel Draw X7 and their functions to students so they know how to make calligraphy through the Corel Draw X7 application. Utilization of the CorelDraw X7 software application program can improve students' soft skills and creativity. So they can pose as they want.